2017
DOI: 10.1007/s00705-017-3576-x
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infection in savanna chimpanzees (Pan troglodytes schweinfurthii) in the Issa Valley, Tanzania

Abstract: Adenoviruses are a widespread cause of diverse human infections with recently confirmed zoonotic roots in African great apes. We focused on savanna-dwelling chimpanzees in the Issa Valley (Tanzania), which differ from those from forested sites in many aspects of behavior and ecology. PCR targeting the DNA polymerase gene detected AdV in 36.7% (69/188) of fecal samples. We detected five groups of strains belonging to the species Human mastadenovirus E and two distinct groups within the species Human mastadenovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…Despite the fact that many studies focused on PRRS immunoprophylaxis have already been published and many procedures are implemented in the agricultural industry, a universal model does not yet exist (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The use of live attenuated vaccines is generally preferred as was also confirmed in our field study (61).…”
Section: Discussionsupporting
confidence: 60%
“…Despite the fact that many studies focused on PRRS immunoprophylaxis have already been published and many procedures are implemented in the agricultural industry, a universal model does not yet exist (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The use of live attenuated vaccines is generally preferred as was also confirmed in our field study (61).…”
Section: Discussionsupporting
confidence: 60%
“…Captive gorillas in zoos had a much higher prevalence of shedding (36%-100%) [13]. The results in our Senegalese chimpanzee study population (54.2%) were higher than in the Cameroon/Democratic Republic of Congo study (40%) [13] and in another population of savannah-dwelling chimpanzees from the Issa Valley in Tanzania (37%) [35], and they were lower than the reported rate of 68% in the Republic of Congo [31]. These differences seem to be marginal and could be due to differences in sample collection and conservation conditions, study region, seasonality or degree of anthropogenic disturbance of the habitat, but they are less likely to be due to laboratory differences, since all the studies used the same PCR assay [13].…”
Section: Discussioncontrasting
confidence: 53%
“…Sequencing using BioEdit and comparison using BLAST24.Wang et al [47]USA, 2018Nasal swabs from human subjects with influenza like illness who were living in close proximity to dense poultry and swine farming operations were examined for evidence of panspecies adenoviruses. No evidence of zoonotic adenoviruses was found.Molecular: PCR targeting hexon gene25.Dadáková et al [48]Tanzania, 2018Fecal samples from unhabituated eastern chimpanzees demonstrated HAdV-B, -C and -E strains; however, all were distinct from human, even gorilla and bonobo clusters, indicating strict host specificity of the virusesPhylogenetic: PCR targeting DPOL gene partial DPOL and/or hexon sequencing; ClustalW amino acid alignment; BLAST analysis and hexon-based phylogenetic analysisaa = amino acid; Abs = antibodies; AdV = adenovirus; AdV-2 = adenovirus serotype 2; AdV-C1 = adenovirus species C serotype 1; AdV-C6 = adenovirus species C serotype 6; AdV-C68 = adenovirus species C serotype 68; BaAdV = baboon adenovirus; BaAdV -1, -2, -3, and -4 = baboon adenoviruses serotypes 1, 2, 3 and 4; BLAST = Basic Local Alignment Search Tool; CAR = Central African Republic; CELO = chicken embryo lethal orphan; DBP = DNA-binding protein; DPOL = DNA polymerase gene; DRC = Democratic Republic of the Congo; HAdV = human adenovirus; HAdV-2 = human adenovirus serotype 2; HAdV-3 = human adenovirus serotype 3; HAdV-4 = human adenovirus serotype 4; HAdV-41 = human adenovirus serotype 41; HAdV-52 = human adenovirus serotype 52; HAdV-B = human adenovirus species B; HAdV-B7 = human adenovirus species B serotype 7; HAdV-B16 = human adenovirus species B serotype 16; HAdV-B21 = human adenovirus species B serotype 21; HAdV-B50 human adenovirus species B serotype 50; HAdV-C = human adenovirus species C; HAdV -E = human adenovirus species E; HAdV-E4 = human adenovirus species E serotype 4; HAdV-F = human adenovirus species F; HAdV-G = human adenovirus species G; ILI = influenza-like-illness; ITR = inverted terminal repeat; MAFFT = multiple alignment using fast Fourier transform; MEGA4 = Molecular Evolutionary Genetics Analysis version 4.0; PCR = polymerase chain reaction; pTP = terminal protein precursor; SAdV = simian adenovirus; SAdV-E25 = simian adenovirus species E serotype 25; TMAdV = titi monkey adenovirus.*Note that Dehghan et al [40] was published after the systematic review search, but has been included in this table due to relevance to the review.…”
Section: Resultsmentioning
confidence: 99%